Réponses

2013-04-07T10:00:46+02:00

Alors,

 

10^-2 * 10^-2 / 10 = 10^-4 / 10 = 10^-5

 

10^6 * 10^-7 / 10^-5 = 10^-1 / 10^-5 = 10^4

 

10^6 / 10^4 * 10^-7 = 10^6 / 10^-3 = 10^9

 

10^8 / 10^3 * 10^-12 = 10^8 / 10^-9 = 10^17

 

10^-3 * 10^8 / (10^-3)^-3 = 10^5 / 10^9 = 10^-4

 

10^3 * 10^-4 / 10^-2 * 10^5 = 10^-1 * 10^3 = 10^-4

 

10^7 * 10^6 / 10^-1 * 10^-8 = 10^13 / 10^-9 = 10^22

 

10^2 * 10^-7 * 10 / 10^3 * (10^-2)^4 = 10^-4 / 10^-3 = 10^1 = 10

 

 

3b^2 * b^3 = 3b^5

 

4b^3 * 5b^4 = 20b^7

 

2b^5 * 3b^2 = 6b^3

 

3b^5 / b^2 = 3b^3

 

6b^4 / 2b^3 = 3b^1

 

1 /2b^2 = 1/2b^-2

 

(4b)^2 = 16b^2

 

(2b)^3 = 8b^3